Q: Which expression has a value of 27 when n equals 2?

Write your answer...

2 squared is 4 3 cubed is 27 27 plus 4 is 31

It would help if the expression was given!

Given a value of x, find the value for -3x + 2

(60 - 2*27) + 9/3 = 9

Firstly divide 27 by 3.14 to get the diameter. Then divide that by two to get the radius. Then square that and multiply by 3.14 to get the area. You get the following mathematical expression: [(27/3.14)/2]^2∙3.14 Firstly divide 27 by 3.14 which is approximately 8.6. The expression is now: [8.6/2]^2∙3.14 Now divide 8.6 by 2 which equals 4.3. The expression is now: 4.3^2∙3.14 Then square 4.3 which equals 18.49. The expression is now: 18.49∙3.14 That equals 58.0586. Threfore the area is 58.0586 ft^2 if pi is rounded to 3.14.

7h - 2 - 51 is an expression NOT an equation. An expression cannot be solved for the value of a variable.

If the expression is (x - y)2, the solution is (7 - -2)2 = (7+2)2 = 92 = 81. If the expression is x - y2, the solution is 7 - (-2)2 = 7 - 4 = 3.

x=25

in maths, an expression is an equation with no equals sign. equation.............2+2=4 expression..........2+2

76-2*6=444

5(5) is 25. 3(-2) is (-6). The expression becomes 25 - (-6). When subtracting a negative number, you actually "add the opposite," so the expression is now 25 + 6 (positive 6 is "the opposite" of -6); the value is 31.

y = -26

Yes.

It is an equation ... Anything with an equals is an equation 2+b=6 Anything without an equals is an expression 2+a

10

x=-2

If you mean: x^2+15-3x then its value is 19 when x equals 4

3*9 + 2 and that would be 27 + 2 which, in turn is 29.

2(2)2 + 3(2)(- 4) - 4(- 4)2 8 - 24 - 64 = - 80 ======

-3/2

no

You take the expression and, wherever there is the variable n in the expression, you substitute 12. Wherever there is m, you substitute 4. Then you evelaute the expression.For example n2 - 2mn + 27m = 122 - 2*4*12 + 27*4 = 144 - 96 + 108 = 156

2x^2+3xy-4y2(4)+3(2)(-4)-(4)(-4)8-24+16=0

Since there is no expression given, there is no sensible answer.

the expression is: 1^2=1 2^2+(2-1)^2=5 3^2+(3-1)^2+(3-2)^2=14